Solvent-Free Hydrodeoxygenation of Triglycerides to Diesel-like Hydrocarbons over Pt-Decorated MoO2 Catalysts - Sisira Fangkoch; Sutida Boonkum; Sakhon Ratchahat; Wanida Koo-amornpattana; Apiluck Eiad-Ua; Worapon Kiatkittipong; Wantana Klysubun; Atthapon Srifa; Kajornsak Faungnawakij; Suttichai Assabumrungrat (My University, 2020)
In the present work, the solvent-free hydrodeoxygenation of palm oil as a representative triglyceride model compound to diesel-like hydrocarbons was evaluated in a batch reactor using Pt-decorated MoO2 catalysts. The catalysts with various Pt loadings (0.5–3%) were synthesized by an incipient wetness impregnation method. The metallic Pt and MoO2 phases were detected in the XRD patterns of as-prepared catalysts after the reaction and acted as active components for the deoxygenation reactions. The XPS experiments confirmed the existence of metallic Pt and PtOx species. The XANES investigation of Mo L3-edge spectra elucidated a change in the valence state by the transformation of MoO3 into MoO2 species after the deoxygenation reaction. The TEM observation revealed the formation of Pt nanoparticles in the range of 1–3 nm decorated on MoO2 species. The number of acid sites increased with stronger metal–support interactions on increasing the Pt loading. The catalytic performance of the MoO2 catalyst significantly improved with a small amount of Pt decoration. However, the further increase in Pt loading did not relatively increase the deoxygenation activity due to the formation of the agglomerated Pt particles. The high performance of the decorated catalysts could be attributed to the moderate acidity from the Pt dispersed on MoO2 toward decarbonylation and decarboxylation reactions.
Keywords: Hydrodeoxygenation; Vegetable oil refining; Catalysis and Hydrodesulfurization Studies